When the spell is broken: gentrification, urban tourism and privileged discontent in the Amsterdam canal district. (July 2017) - Pinkster, Fenne M; Boterman, Willem R
Expansion of urban tourism in historic districts in European cities is putting increasing pressure on these areas as places to live. In Amsterdam, an ever-growing number of tourists visit the famous canal district, which also forms the home of a group of long-term, upper-middle-class residents. While such residents are generally depicted as instigators of urban transformation, in this case, they are on the receiving end. Bringing together the literature on the socio-spatial impact of tourism, belonging and the lived experience of place, this article explores the changing relationship between these established residents and their neighbourhood and provides insight into their growing sense of discontent and even powerlessness in the face of neighbourhood change.